Melodies of Self-Love on Selena Gomez’s Songs: A Semiotic Analysis - Widhayanti, Wahyu Rosyita; Amalia, Syahara Dina (Universitas Pahlawan Tuanku Tambusai, 2025)
This research examined the depiction of self-love in Selena Gomez's music through the lens of Roland Barthes' Semiotic analysis model. A qualitative descriptive research was executed to analyse four songs namely: